Design optimization and precision requirements of an endcap ion trap for single-ion optical clock applications - Chaowei Wang; Shaoyang Dai; Yani Zuo; Fang Fang (AIP Advances)
Ion traps serve as the venue for confining ions and exciting ionic transitions in ion optical clocks, where the geometric dimensions of the electrodes within the ion trap directly impact the performance metrics of the ion optical clocks. In this study, the finite element analysis method was employed to simulate the relationship between the electric field distribution and the dimensions of the electrodes in an endcap ion trap. The simulation data were subjected to curve fitting, with trap depth and potential anharmonicity utilized as the primary evaluation criteria for optimizing ion trap design. The results indicate that the ion trap demonstrates optimal performance when the distance between the radio frequency electrodes is reduced to 0.686 mm, and it is suggested that the chamfer width of the endcap electrode extension be 0.6 mm. Based on this, the study further explored the machining accuracy of certain dimensions, concluding that the required high machining accuracy values for the radio frequency electrodes and the endcap electrodes are ±3 and ±7 μm, respectively, while the aperture machining accuracy requirements are ±3 and ±22 μm, respectively. In addition, the simulation results suggest that a conical surface on the radio frequency electrodes with a height of ∼0.08 mm aids in reducing anharmonicity, although a spherical end surface does not notably improve the electric field distribution. These findings provide a valuable reference for the optimized design and machining of ion traps.